NGHIÊN CỨU CHẾ TẠO SƠN TRONG SUỐT ĐIỆN TỪ SỬ DỤNG TRONG ĐIỀU KIỆN KHÍ HẬU NHIỆT ĐỚI - Hà, Hữu Sơn; Trần, Thị Thu Hằng; Nguyễn, Văn Vinh; Nguyễn, Hồng Phong; Tăng, Xuân Dương; Nguyễn, Hồng Thanh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
RESEARCH ON MANUFACTURING ELECTROMAGNETIC TRANSPARENT PAINT SUITABLE FOR USE IN THE TROPICAL CLIMATEElectromagnetic transparent paint is a specialized paint that has the high protection ability and does not affect the transmission of electromagnetic waves through the paint coating. We have studied and selected the main materials available on the market such as Der 671, pigment Cr2O3, anthraquinone red 177, talc powder and have successfully manufactured the radar-transparent paint called RTP.VN which met the requirements of GOST 24709-81 standard. We have also studied the effect of the anti UV additive content on the properties of the RTP.VN paint. The result showed that the suitable amount of anti UV additive in the RTP.VN paint did not affect its electromagnetic transparency and significantly improved its durability as well. The accelerated test was conducted in order to compare the properties of both RTP.VN paint and the similar ЭП-140 paint.